Investigation of Glutamine and GABA Levels in Patients With Idiopathic Generalized Epilepsy Using MEGAPRESS - Chowdhury, Fahmida A. (J Magn Reson Imaging, 2014)
PURPOSE: Idiopathic generalized epilepsies (IGE) comprise a group of clinical syndromes associated with spike wave discharges, putatively linked to alterations in neurotransmission. The purpose of this study was to investigate whether patients with IGE have altered glutamine and γ-aminobutyric acid (GABA) levels indicative of altered excitatory and inhibitory neurotransmission in frontal regions. MATERIALS AND METHODS: Single-voxel MEGA-edited PRESS magnetic resonance imaging (MRI) spectra were acquired from a 30-mL voxel in the dorsolateral prefrontal cortex in 13 patients with IGE (8 female) and 16 controls (9 female) at 3T. Metabolite concentrations were derived using LCModel. Differences between groups were investigated using an unpaired t-test. RESULTS: Patients with IGE were found to have significantly higher glutamine than controls (P = 0.02). GABA levels were also elevated in patients with IGE (P = 0.03). CONCLUSION: Patients with IGE have increased frontal glutamine and GABA compared with controls. Since glutamine has been suggested to act as a surrogate for metabolically active glutamate, it may represent a marker for excitatory neurotransmission.